Brain Tumors - Agrawal, Amit (IntechOpen, 2022)
Brain tumors comprise a spectrum of histological patterns. Their presentation and management depend on their location, size, and grade of lesions. This book is a collection of high-quality research work from global experts on brain tumors, including meningiomas, and their treatment.